(untitled) (Zaporizhzhia Historical Review, 2021)
On the base of the original archive sources the unknown pages of the history of the relations between the Orthodox Church and the Soviet State in Zaporozhzhya region are shown. The author studies the character of these relations under the influence of the Ukrainian revolution from the moment of the first establishment of the Soviet power – in the beginning of 1918 till the time of its formal consolidation at the beginning of 1920. The dependence of these relations on the ideological arrangements of the Bolshevik’s party, the general political course of the government, the military-political situation and the traditional religiosity of the population are also under consideration here.